Electromobility in Norway: Experiences and Opportunities. (August 2015) - Figenbaum, Erik; Assum, Terje; Kolbenstvedt, Marika
Abstract: Electrification will reduce environmental impacts and greenhouse gas emissions from transport. Electric propulsion is energy efficient, and does not cause local pollution. In 2013 the new vehicle market share of electric vehicles (EVs) was 5.8%. and 80% were owned by private consumers. This paper explores some possible explanations to the Norwegian development by describing the electromobility story, the incentives given and the attitudes among users. A long lasting interaction between private enterprises, public authorities and non-government organizations combined with a taxation system that gives the authorities opportunity to influence vehicle purchase, and to compensate for marketing challenges related to price, have supported the Norwegian diffusion of electromobility. In addition a high share of multi-vehicle households and a publicly supported expansion of charging stations have made range challenges manageable. The Norwegian market is expected to continue to grow as more models are coming into the market and given the governmental decision to extend the economic incentives until the end of 2017. Rapid development of the technology and policies makes firm conclusions for other countries challenging to make. Further research should include several countries and broader cost/benefit and life-cycle analyses.